2016
DOI: 10.1016/j.neuropharm.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Rat intra-hippocampal NMDA infusion induces cell-specific damage and changes in expression of NMDA and GABAA receptor subunits

Abstract: Excessive stimulation of NMDA receptors with glutamate or other potent agonists such as NMDA leads to excitotoxicity and neural injury. In this study, we aimed to provide insight into an animal model of brain excitotoxic damage; single unilateral infusion of NMDA at mild dose into the hippocampal formation. NMDA infusion induced chronic, focal neurodegeneration in the proximity of the injection site. The lesion was accompanied by severe and progressive neuroinflammation and affected preferentially principal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The excitotoxic effect of QA is influenced by NMDAR subunit composition5253 and modulated by metabotropic glutamate receptors54. QA shares with NMDA its property to damage preferentially pyramidal neurons, while sparing other neuron types55. Notably, QA has been shown to produce oxidative damage, independent of its activity at the NMDAR, by forming complexes with Fe 2+ that mediate the generation of reactive oxygen species (ROS)5657.…”
Section: Discussionmentioning
confidence: 99%
“…The excitotoxic effect of QA is influenced by NMDAR subunit composition5253 and modulated by metabotropic glutamate receptors54. QA shares with NMDA its property to damage preferentially pyramidal neurons, while sparing other neuron types55. Notably, QA has been shown to produce oxidative damage, independent of its activity at the NMDAR, by forming complexes with Fe 2+ that mediate the generation of reactive oxygen species (ROS)5657.…”
Section: Discussionmentioning
confidence: 99%
“…To explore this possibility, we injected either N-methyl-D-aspartic acid (NMDA) or bicuculline into the right dorsal hippocampus. Hippocampal injection of NMDA stimulates ionotropic NMDA receptors, induces acute excitotoxicity and status epilepticus; however, unlike KA-induced status epilepticus, does not cause an early loss of hippocampal interneurons 22,36 . Bicuculline is a competitive antagonist of GABA A receptors and it is known to produce seizures in the absence of neurodegenerative events 37 .…”
Section: Status Epilepticus Induces Changes In the Expression Of Par mentioning
confidence: 99%
“…After 14 days of expression, animals were sacrificed, and their brain processed for the gene expression and fluorescent microscopy analyses. Histology and immunohistochemistry were performed as described in our previous work 22,23 . Brain sections were stained with the following antibodies: GFAP (DAKO Schweiz, Z334, 1:20000), Iba-1 (Wako, 019-19741, 1:3000) and NeuN (Chemicon, MAB377, 1:1000).…”
mentioning
confidence: 99%
“…NMDA receptors are a subtype of ionic glutamate receptors, and are characterized of high permeability to calcium ions (18). Considerable literature has demonstrated that calcium influx via NMDA receptor is the key step in glutamate-induced excitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for NMDA that are ligand-gated ion channels play a critical role in NMDA-induced neurotoxicity (17). The activation of NMDA receptors is identified by the influx of Na + , Cl − , Ca 2+ ions, which are examined by whole-cell patch clamp recording in cultured hippocampal neurons (18). The NMDA-elicited currents were measured in Mg 2+free solution containing Ca 2+ (2 mM), with 2-minute bath perfusion after NMDA current was recorded.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%